Melatonin inhibits glucocorticoid receptor nuclear translocation in mouse thymocytes - Presman, Diego Martin (2006)
The antiapoptotic effect of melatonin (MEL) has been described in several systems. In particular, MEL inhibits glucocorticoid-mediated apoptosis. Our group previously demonstrated that in the thymus, MEL inhibits the release of Cytochrome C from mitochondria and the dexamethasone-dependent increase of bax mRNA levels. In this study we analyzed the ability of MEL to regulate the activation of the glucocorticoid receptor (GR) in mouse thymocytes. We found that even though the methoxyindole does not affect the ligand binding capacity of the receptor, it impairs the steroid-dependent nuclear translocation of the GR and also prevents transformation by blocking the dissociation of the 90-kDa heat shock protein. Coincubation of the methoxyindole with dexamethasone did not affect the expression of a reporter gene in GR-transfected Cos-7 cells or HC11 and L929 mouse cell lines that express Mel-1a and retinoid-related orphan receptor-alpha (RORalpha) receptors. Therefore, the antagonistic effect of MEL seems to be specific for thymocytes, in a Mel 1a- and RORalpha-independent manner. In summary, the present results suggest a novel mechanism for the antagonistic action of MEL on GR-mediated effects, which involves the inhibition of 90-kDa heat shock protein dissociation and the cytoplasmic retention of the GR.